2019
DOI: 10.1111/ocr.12288
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the root to crown ratios of the permanent dentition

Abstract: Structured Abstract Objective Root resorption due to orthodontic tooth movement may adversely affect the root‐crown (R/C) ratios of permanent teeth, especially in patients with Short Root Anomaly (SRA), a poorly understood disorder affecting root development. Evaluation of SRA R/C ratios to normal dentition would facilitate diagnosis and orthodontic treatment planning. However, reference values are not available for all ethnicities. Our goal was to determine R/C ratios of permanent teeth and their relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
0
17
0
1
Order By: Relevance
“…Therefore, it may be speculated that adopting raw material thickness and height of 3Dprinted models may be advantageous to better control the material thickness properties of thermoformed aligners, and eventually the resulting force systems. Additionally, as crown height varies among patients [38], clinicians should also carefully consider that higher crowns may lead to reduced thickness values, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be speculated that adopting raw material thickness and height of 3Dprinted models may be advantageous to better control the material thickness properties of thermoformed aligners, and eventually the resulting force systems. Additionally, as crown height varies among patients [38], clinicians should also carefully consider that higher crowns may lead to reduced thickness values, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Further non-compliance, round tripping movements, and movements near the bone cortex might also be associated with lower orthodontic tooth movement rates and/or extended treatment times [ 45 , 51 ]. Even considering these reflections, heterogeneity between study designs, ethnic differences, and the differences within phenotypic characterization might contribute to some of the observed results [ 17 , 23 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, differences observed between study results in terms of the diagnostic, clinical, and genetic factors associated with EARR of different degrees are a major concern that should be addressed. With respect to this, it seems plausible that the heterogeneity found between study designs, ethnic differences [ 52 ], absence of a standardized and unique phenotypic characterization of EARR in terms of diagnostic methods and diagnostic criteria values/thresholds between studies might have contributed to some of this controversy. Nevertheless, this is a critical issue that should be clearly revisited and global consensus-based standards should be achieved in this regard to grant a next generation improvement, not only in internal validity of the studies but equally critical, in external validity of the research in the field.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of Wang et al has found a significant ethnic result in terms of crown root ratio after orthodontic treatment between three different ethnic groups; Hispanic patients had lower mean root crown ratios in most teeth compared to both the Caucasians and African Americans (Wang et al, 2019).…”
Section: Ethnicitymentioning
confidence: 95%